Bundling of Services and Household Welfare in Developing Countries Using Panel Data: The Case of Peru - Alberto Chong; Jesko Hentschel; Jaime Saavedra-Chanduví (Inter-American Development Bank, Research Department, 2004)
Using panel data for Peru for the period 1994-2000, we find that when households receive two or more services jointly, the welfare increases of the household, as measured by changes in consumption, are larger than when services are provided separately. Such an increase appears to be more than proportional, as F-tests on the coefficients of the corresponding regressors confirm. Thus, we find that bundling of services may help realize welfare effects.
Keywords: O1; O2; 330; Bundling; Expenditures; Public Services; Welfare; Panel Data; Versorgungswirtschaft; Leistungsbündel; Wohlfahrtsanalyse; Panelforschung; Entwicklungsländer; Peru